Model Development of History Teaching Materials Local History Based for High School With SOI Approach - Djono, Djono (The Indonesian Journal of Social Studies, 2025)
The aims of this study were to: ( 1) find out the substance of local history material in Indonesian history teaching materials used in SMA Surakarta; ( 2) Constructing the development of Indonesian history teaching materials based on local content; and ( 3) Testing the effectiveness of local content-based Indonesian history teaching materials using the Selecting, Organizing and Integrating (SOI) approach in history learning at class XI Surakarta Senior High School in increasing understanding of local history. To achieve these goals in this study used research and development methods or Research and Development (R&D). The R & D method is a research method used to produce certain products, and test the effectiveness of products. The R & D method is considered the most appropriate for this research problem. This research seeks to make products in the form of local content-based history teaching materials, as well as to test the effectiveness of using these teaching materials in learning Indonesian history according to the specified targets and criteria. This research was carried out in 4 stages , namely: (1) Exploration; (2) Model development; ( 3) Model testing; and (4) Dissemination . The results of the study show that : ( 1) The quality of Indonesian history teaching materials in high schools that have been used so far only includes material substance from basic competencies in the national curriculum. The existing teaching materials are based on a grid that has been developed in BSNP which emphasizes national political events, while local history materials have not been accommodated in teaching materials. Based on the KTSP rules, teachers can develop teaching materials according to the potential of their region. ( 2) Development of teaching materials by combining local history in the Surakarta area with existing materials and teaching materials based on the national curriculum starting from: (a) Preliminary study to determine needs; (b) Development of prototypes using the SOI. Local history material is selected from oral sources and artefact sources and integrated with national curriculum material so that teaching materials based on local content are structured; (c) An expert assessment is carried out on prototypes of teaching materials and other products developed including the instruments used to measure the effectiveness of teaching materials; (d) Limited tests and broad tests were carried out on instruments and products with a larger number of schools; and (e) Finalization. ( 3) From the results of the effectiveness test it is known that the use of local content-based history teaching materials can improve students' understanding of history in high school as evidenced by the results of the one-way ANOVA test between the experimental class and the control class . It is hoped that research will contribute to the development of history learning, especially in local history learning through the development of teaching materials. Teachers can use this research product as a reference in developing history teaching materials based on local content.